Risk-Taking Propensity and Sensation Seeking in Survivors of Adverse Childhood Experiences. Issue 19 (October 2021) - Babad, Sara; Zwilling, Amanda; Carson, Kaitlin Walsh; Fairchild, Victoria; Razak, Shanna; Robinson, Gabriella; Nikulina, Valentina
Risk-taking propensity and sensation seeking are developmentally meaningful traits for emerging adults, individuals ages 18 to 25 years. Adverse childhood experiences (ACEs) of childhood abuse and neglect, exposure to domestic violence, residing with a substance abusing or mentally ill caregiver, and growing up with an incarcerated family member negatively impact the well-being of emerging adults. However, the specific association between ACEs and risk-taking propensity and sensation seeking has not been previously examined in this age group. This study aims to determine whether ACEs are individually or cumulatively related to risk-taking propensity (assessed by the Domain-Specific Risk-Taking Scale) and sensation seeking (assessed by the Behavior Inhibition System/Behavior Approach System Scales) in a diverse sample of undergraduates, n = 436; M age = 19.73 years ( SD = 1.83 years); 67% female; 22% Hispanic. Multivariate ordinary least squares regressions were run to examine the association between ACEs and risk-taking propensity and sensation seeking. Individually, emotional abuse predicted greater inhibition ( B = .28, p < .001), growing up with a mentally ill family member ( B = –.12, p < .05) and emotional neglect ( B = –.13, p < .05) predicted reduced motivation to pursue rewarding cues, and emotional neglect ( B = –.12, p < .05) and witnessing domestic violence ( B = –.10, p < .05) predicted less reward responsiveness. No cumulative effects were found. ACEs related to environmental instability may have a unique impact on sensation seeking domains in emerging adults. Clarifying the role of sensation seeking in emerging adults can contribute to better understanding of risk and resilience factors in this vulnerable population.